Emergy-based ecological footprint analysis for a mega-city: The dynamic changes of Shanghai. (10th February 2019) - Pan, Hengyu; Zhuang, Mufan; Geng, Yong; Wu, Fei; Dong, Huijuan
Abstract: To move towards sustainable urban development, interactions between economic and ecological systems should be further investigated due to their coupled relations. In this study, we propose an emergy-based ecological footprint (EEF) analysis framework. Shanghai was selected as a case study city to see its dynamic changes from 2007 to 2016. The results show that Shanghai had a large ecological deficit, an extremely high ecological footprint intensity and a poor coordination relationship between its ecological system and its economic system, indicating a great ecological challenge that it is facing. The uneven distribution of its emergy ecological footprint is mainly due to the large share of fossil fuels land type. But with the city's great efforts, the overall ecological pressure has been reduced and the coordination relationship has also been improved, while the local economy is still booming. Pearson correlation analysis further indicates that the city's policy on developing tertiary industry has resulted in a positive effect on improving the coordinating relationship. The ratio between the output value of heavy industry and gross industrial output value has the most negative correlation with the coordinating relationship. Finally, policy recommendations are raised by considering the local realities. These recommendations can also provide valuable insights to other megacities with similar challenges. Highlights: A modified emergy ecological footprint method was proposed. Emissions' impact was integrated into EEF method. Shanghai faces enormous ecological pressure. Shanghai is moving towards ecological sustainability.